The impact of leadership on employees’ performance while working remotely, a case study of DEWA in Dubai - ALFARDAN, AMEER JASSIM ZAINAB (2023)
The current investigation sets out to discover the impact of varying leadership approaches on staff performance at DEWA amidst the “COVID-19” pandemic, a time marked by an upsurge in “remote work”. We focused our attention on four distinctive leadership styles: “transformational”, “transactional”, “autocratic”, and “laissez-faire”. Moreover, we considered the potential moderating effects of “intrinsic motivation” and the equilibrium between work and personal life. Our findings reveal that “transformational leadership” played a substantial role in boosting “employee performance” and promoting a healthy “work-life balance”. “Transactional leadership” displayed a marginal influence on “employee performance”, while autocratic and “laissez-faire leadership” styles demonstrated no noteworthy effects. A fascinating finding was the positive moderating role of “intrinsic motivation”, which intensified the correlation between “transformational leadership” and “employee performance”. The implications of this study underscore the need to embrace “transformational leadership” practices at DEWA in order to cultivate a more efficient “remote working” atmosphere in the post-COVID landscape. Furthermore, it highlights the importance of fostering “intrinsic motivation” within the workforce to achieve improved performance results. Future research endeavors are encouraged to delve into other leadership styles and potential moderating factors within similar contexts of “remote work”.